The prognostic value of advanced lung cancer inflammation index (ALI) in elderly patients with heart failure - Yuan, Xiao; Huang, Bi; Wang, Ruiyu; Tie, Hongtao; Luo, Suxin (Frontiers in Cardiovascular Medicine, 2022)
Purpose The advanced lung cancer inflammation index (ALI) is a novel inflammatory and nutritional index that exerts prognostic value in various types of cancer. A previous study demonstrated that ALI at discharge could predict the prognosis in patients with acute decompensated heart failure (ADHF). However, the long-term prognostic value of ALI on admission in elderly heart failure (HF) inpatients remains unclear. Materials and methods We retrospectively collected HF inpatients over 65-year-old who were hospitalized in our cardiology center during the whole year of 2015. ALI was calculated as body mass index (BMI) × serum albumin (Alb)/neutrophil-to-lymphocyte ratio (NLR). Patients were divided into two groups by the optimal cutoff value of ALI for predicting all-cause mortality using time-dependent receiver operating characteristic (ROC) curves. The Spearman rank correlation coefficient was computed to evaluate the correlation between ALI and the geriatric nutritional risk index (GNRI). Kaplan–Meier curves, Cox survival analyses, time-dependent ROC analyses, and net reclassification improvement (NRI) analyses were used to assess the prognostic effect of ALI on all-cause mortality and cardiovascular mortality. Results Over a 28-month median follow-up, all-cause and cardiovascular mortality occurred in 192 (35.4%) and 132 (24.3%) out of 543 patients, respectively. The optimal cutoff value of ALI for predicting all-cause mortality at 2 years was 25.8. Spearman’s correlation coefficient showed a moderate positive linear correlation between ALI and GNRI (r = 0.44, p < 0.001). The Kaplan–Meier analysis revealed that the cumulative incidences of both all-cause and cardiovascular mortalities were significantly higher in patients with lower ALI (log-rank test, all-cause mortality: p < 0.0001; cardiovascular mortality: p < 0.0001). The multivariate Cox proportional hazard analyses indicated that ALI was an independent predictor for both all-cause mortality (HR 0.550, 95% CI 0.349–0.867, p = 0.01) and cardiovascular mortality (HR 0.536, 95% CI 0.302–0.953, p = 0.034). Time-dependent ROC analyses showed that ALI was comparable to GNRI in predicting long-term all-cause mortality (AUC: ALI 0.625, GNRI 0.641, p = 0.976) and cardiovascular mortality (AUC: ALI 0.632, GNRI 0.626, p = 0.999) at 2 years. However, the estimated NRI indicated that the addition of ALI could not significantly improve risk stratification of base models for all-cause mortality (categorical NRI 4.9%, p = 0.433, continuous NRI 25%, p = 0.022) or cardiovascular mortality (categorical NRI 6.5%, p = 0.223, continuous NRI 27.5%, p = 0.029). Conclusion Higher ALI was significantly associated with lower all-cause and cardiovascular mortalities in elderly HF patients. ALI on admission could be a competent nutrition-inflammation marker with independent predictive value for evaluating the long-term mortality of HF in elder population.